2009
DOI: 10.1038/leu.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Bcr-Abl-mediated redox regulation of the PI3K/AKT pathway

Abstract: Bcr-Abl causes chronic myelogenous leukemia, a myeloproliferative disorder characterized by clonal expansion of hematopoietic progenitor cells. In this study, inducible expression of Bcr-Abl in TonB.210 cells is associated with increased production of intracellular reactive oxygen species (ROS), which is thought to play a role in survival signaling when generated at specific levels. Elevated ROS in Bcr-Abl-expressing cells were found to activate PI3k/Akt pathway members such as Akt and GSK3b as well as downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 37 publications
6
130
1
1
Order By: Relevance
“…In this regard, it has recently been shown that the inhibition of PP1a by ROS leads to the constitutive activation of the PI3K/ AKT pathway in leukaemic cells. 33 In addition, it has been shown that ROS are also important for platelet release, 34 this points to the importance of ROS not only in triggering differentiation programmes but also in terminal platelet release from mature megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has recently been shown that the inhibition of PP1a by ROS leads to the constitutive activation of the PI3K/ AKT pathway in leukaemic cells. 33 In addition, it has been shown that ROS are also important for platelet release, 34 this points to the importance of ROS not only in triggering differentiation programmes but also in terminal platelet release from mature megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%
“…NOX-originated ROS have been documented to have multiple effects on leukemia cell proliferation and survival (13,19,27). Leukemic oncogenes have been shown to regulate either the expression of NOX components or the availability of their substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of ROS also result from the expression of oncogenes (19,20). The BCR-ABL translocation that results in chronic myelogenous leukemia (CML) has been shown to increase ROS levels in both BCR-ABL-transformed hematopoietic cell lines and primary CML cells (21)(22)(23). Mutations within the BCR-ABL tyrosine kinase domain that lead to resistance to imatinib as well as to other manifestations of DNA damage are accelerated by ROS generation and reduced by the concomitant administration of antioxidants (23).…”
mentioning
confidence: 99%